Recent advances in magnetic molecularly imprinted polymers for perfluorooctanoic acid detection and removal: The critical role of thiol functionality - Khan, Noor Mohammad; Khan, Sulaiman; Muhammad, Taj; Fatima, Areej; Nurlin, Abu Samah (Malaysian Institute of Chemistry, 2026)
Perfluorooctanoic acid (PFOA), a persistent PFAS compound, has driven strict regulations and increased demand for effective detection and remediation technologies. Magnetic molecularly imprinted polymers (MMIPs) have emerged as a promising solution, particularly those incorporating thiol-containing functional groups. This review summarizes recent progress in MMIPs designed for the removal and sensing of PFOA. Molecular imprinting combined with magnetic nanoparticles enables selective recognition and facilitates simple magnetic separation. Thiol groups, including perfluorinated thiols, create fluorophilic binding sites via van der Waals and dipole–dipole interactions between fluorine-rich polymer surfaces and the PFOA tail, while also forming hydrogen bonds with the PFOA carboxyl group. Thiol monomers allow stable surface grafting, compatibility with mild polymerization, and improved structural durability during regeneration. Advances in synthesis, including core–shell architectures, novel thiol monomers, optimized polymerization, and greener fabrication methods, have increased binding capacity and selectivity. MMIP-based sensing platforms—including electrochemical, optical, and photoelectrochemical devices—now achieve detection limits from sub-parts per trillion to tens of parts per trillion. Pilot-scale water treatment studies demonstrate the effectiveness of magnetic recovery and reuse over multiple cycles. Emerging trends include dual-functional monomers, stimuli-responsive systems, and hybrid MIP–carbon materials. Remaining challenges involve scaling production, managing matrix interferences, and standardizing testing protocols.